2004
DOI: 10.1016/j.jhsb.2004.06.012
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cellular Proliferative Activity on Recurrence and Local Tumour Extent of Localized Giant Cell Tumour of Tendon Sheath

Abstract: This study investigates whether the proliferative activity of giant cell tumour of tendon sheath is related to its recurrence rate and local aggressiveness. The clinicopathological and immunohistochemical features of 30 localized giant cell tumours of tendon sheath were studied and the influence of the MIB-1 staining index on recurrence, tumour extent around the phalanx and involvement of the bone were evaluated. No significant difference in the MIB-1 staining index was found between the lesions which recurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 19 publications
1
45
0
4
Order By: Relevance
“…However, Kitagawa et al [8] did not support this theory. The authors advocated that bone involvement in patients with localised GCTTS was due to simple erosion, caused by the pressure effect of the tumour, and was not a true invasion.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, Kitagawa et al [8] did not support this theory. The authors advocated that bone involvement in patients with localised GCTTS was due to simple erosion, caused by the pressure effect of the tumour, and was not a true invasion.…”
Section: Discussionmentioning
confidence: 95%
“…In total, 14.8% of patients had tumour recurrence (83/559 patients) [1,5,6,8,9,15,18,20,23]. Fourteen patients where local irradiation was applied did not experience a tumour recurrence but due to the small number of cases this was not statistically significant [9].…”
Section: Resultsmentioning
confidence: 99%
“…Reilly et al (1999) and Grover et al (1998) noticed that bone erosion, as confirmed in plain X-rays, might be a reason for recurrence (8,27). However, Kitagawa (2004) did not support this theory, he advocated the bone involvement was due to simple erosion, caused by the pressure effect of the tumor, and was not a true invasion (11). Lowyck (2006) did not find significant correlation of recurrence with pressure erosions, or degenerative joint disease, neither with the location at the distal interphalangeal joint (28).…”
Section: Discussionmentioning
confidence: 98%
“…1 The proliferative activity in localized nodular form of GCTTS is not related to its high recurrence rate and local aggressiveness. 12 Because of the extreme rarity of the metastasizing form of GCTTS, it is justifiable to adopt a conservative approach when interpreting these atypical features.…”
Section: Discussionmentioning
confidence: 99%